Tìm x
a, x-3/4= 7/5
b, 4/3 -x =1/2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: x=2/5*15=6
b: =>x-7=15
=>x=22
c: =>3/4:x+1/2*4=4
=>3/4:x=4-2=2
=>x=3/8
A) \(x-\dfrac{2}{3}=\dfrac{4}{5}\\ x=\dfrac{4}{5}+\dfrac{2}{3}\)
\(x=\dfrac{22}{15}\)
b)\(\dfrac{7}{9}-x=\dfrac{1}{3}\\ x=\dfrac{7}{9}-\dfrac{1}{3}\\ x=\dfrac{4}{9}\)
C)\(x:\dfrac{2}{3}=\dfrac{9}{8}\\ x=\dfrac{9}{8}x\dfrac{2}{3}\\ x=\dfrac{3}{4}\)
a, \(\dfrac{4x}{7}=\dfrac{1}{5}+\dfrac{2}{3}=\dfrac{3+10}{15}=\dfrac{13}{15}\Rightarrow60x=91\Leftrightarrow x=\dfrac{91}{60}\)
b, \(\dfrac{5}{7}:x=\dfrac{1}{6}+\dfrac{4}{5}=\dfrac{5+24}{30}=\dfrac{29}{30}\Leftrightarrow x=\dfrac{5}{7}:\dfrac{29}{30}=\dfrac{150}{203}\)
a: \(\left(x-4\right)^2-\left(x-3\right)\left(x+3\right)=5\)
\(\Leftrightarrow x^2-8x+16-x^2+9=5\)
\(\Leftrightarrow-8x=-20\)
hay \(x=\dfrac{5}{2}\)
a: \(\Leftrightarrow\left[{}\begin{matrix}x-\dfrac{3}{4}=\dfrac{1}{5}\\x-\dfrac{3}{4}=-\dfrac{1}{5}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{19}{20}\\x=\dfrac{11}{20}\end{matrix}\right.\)
\(a,\left|x-\dfrac{3}{4}\right|=\dfrac{1}{5}\)
\(\Leftrightarrow\left[{}\begin{matrix}x-\dfrac{3}{4}=\dfrac{1}{5}\\x-\dfrac{3}{4}=\dfrac{-1}{5}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{19}{20}\\x=\dfrac{11}{20}\end{matrix}\right.\)
\(b,\dfrac{-1}{3}+\left|x\right|=0,5\)
\(\Leftrightarrow\left|x\right|=\dfrac{5}{6}\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{5}{6}\\x=\dfrac{-5}{6}\end{matrix}\right.\)
Bài 1:
a) Ta có: \(\dfrac{2}{5}\cdot x+\dfrac{1}{3}=\dfrac{1}{5}\)
\(\Leftrightarrow\dfrac{2}{5}\cdot x=\dfrac{1}{5}-\dfrac{1}{3}=\dfrac{-2}{15}\)
\(\Leftrightarrow x=\dfrac{-2}{15}:\dfrac{2}{5}=\dfrac{-2}{15}\cdot\dfrac{5}{2}\)
hay \(x=-\dfrac{1}{3}\)
Vậy: \(x=-\dfrac{1}{3}\)
b) Ta có: \(\dfrac{1}{5}+\dfrac{5}{3}:x=\dfrac{1}{2}\)
\(\Leftrightarrow\dfrac{5}{3}:x=\dfrac{1}{2}-\dfrac{1}{5}=\dfrac{3}{10}\)
\(\Leftrightarrow x=\dfrac{5}{3}:\dfrac{3}{10}=\dfrac{5}{3}\cdot\dfrac{10}{3}\)
hay \(x=\dfrac{50}{9}\)
Vậy: \(x=\dfrac{50}{9}\)
c) Ta có: \(\dfrac{4}{9}-\dfrac{5}{3}\cdot x=-2\)
\(\Leftrightarrow\dfrac{5}{3}x=\dfrac{4}{9}+2=\dfrac{22}{9}\)
\(\Leftrightarrow x=\dfrac{22}{9}:\dfrac{5}{3}=\dfrac{22}{9}\cdot\dfrac{3}{5}\)
hay \(x=\dfrac{22}{15}\)
Vậy: \(x=\dfrac{22}{15}\)
d) Ta có: \(\dfrac{5}{7}:x-3=\dfrac{-2}{7}\)
\(\Leftrightarrow\dfrac{5}{7}:x=\dfrac{-2}{7}+3=\dfrac{19}{21}\)
\(\Leftrightarrow x=\dfrac{5}{7}:\dfrac{19}{21}=\dfrac{5}{7}\cdot\dfrac{21}{19}\)
hay \(x=\dfrac{15}{19}\)
Vậy:\(x=\dfrac{15}{19}\)
a)
\(\Rightarrow\dfrac{47}{10}.x=\dfrac{1}{5}+\dfrac{2}{3}\)
\(\Rightarrow\dfrac{47}{10}.x=\dfrac{3}{15}+\dfrac{10}{15}\)
\(\Rightarrow\dfrac{47}{10}.x=\dfrac{13}{15}\)
\(\Rightarrow x=\dfrac{13}{15}:\dfrac{47}{10}\)
\(\Rightarrow x=\dfrac{13}{10}.\dfrac{10}{47}\)
\(\Rightarrow x=\dfrac{13}{47}\)
b)
\(\Rightarrow\dfrac{5}{7}:x=\dfrac{1}{6}-\dfrac{4}{5}\)
\(\Rightarrow\dfrac{5}{7}:x=\dfrac{5}{30}-\dfrac{24}{30}\)
\(\Rightarrow\dfrac{5}{7}:x=-\dfrac{19}{30}\)
\(\Rightarrow x=\dfrac{5}{7}:\left(-\dfrac{19}{30}\right)\)
\(\Rightarrow x=\dfrac{5}{7}.\left(-\dfrac{30}{19}\right)\)
\(\Rightarrow x=-\dfrac{150}{133}\)
a \(\dfrac{2}{3}x+\dfrac{1}{3}=\dfrac{1}{5}\\ \dfrac{2}{3}x=\dfrac{1}{5}-\dfrac{1}{3}\\ \dfrac{2}{3}x=\dfrac{-2}{15}\\ x=-\dfrac{2}{15}:\dfrac{2}{3}\\ x=-\dfrac{1}{5}\) b) \(\dfrac{4}{5}-\dfrac{5}{3}x=-2\\ \dfrac{5}{3}x=\dfrac{4}{5}+2\\ \dfrac{5}{3}x=\dfrac{14}{5}\\ x=\dfrac{14}{5}:\dfrac{5}{3}\\ x=\dfrac{42}{25}\)c) \(\dfrac{1}{5}+\dfrac{5}{3}:x=\dfrac{1}{2}\\ \dfrac{5}{3}:x=\dfrac{1}{2}-\dfrac{1}{5}\\ \dfrac{5}{3}:x=\dfrac{3}{10}\\ x=\dfrac{5}{3}:\dfrac{3}{10}\\ x=\dfrac{50}{9}\)d) \(\dfrac{5}{7}:x-3=-\dfrac{2}{7}\\ \dfrac{5}{7}:x=3-\dfrac{2}{7}\\ \dfrac{5}{7}:x=\dfrac{19}{7}\\ x=\dfrac{5}{7}:\dfrac{19}{7}\\ x=\dfrac{5}{19}\)
Bài làm :
\(a,x-\frac{3}{4}=\frac{7}{5}\)
\(x=\frac{7}{5}+\frac{3}{4}\)
\(x=\frac{43}{20}\)
\(b,\frac{4}{3}-x=\frac{1}{2}\)
\(x=\frac{4}{3}-\frac{1}{2}\)
\(x=\frac{5}{6}\)
Học tốt nhé
a, \(x-\frac{3}{4}=\frac{7}{5}\)
\(x=\frac{7}{5}+\frac{3}{4}\)
\(x=\frac{43}{20}\)
b, \(\frac{4}{3}-x=\frac{1}{2}\)
\(x=\frac{4}{3}-\frac{1}{2}\)
\(x=\frac{5}{6}\)